Lipotoxicity and immunometabolism in ischemic acute kidney injury: current perspectives and future directions - Otunla, Afolarin A.; Shanmugarajah, Kumaran; Davies, Alun H.; Shalhoub, Joseph (Frontiers in Pharmacology, 2024)
Dysregulated lipid metabolism is implicated in the pathophysiology of a range of kidney diseases. The specific mechanisms through which lipotoxicity contributes to acute kidney injury (AKI) remain poorly understood. Herein we review the cardinal features of lipotoxic injury in ischemic kidney injury; lipid accumulation and mitochondrial lipotoxicity. We then explore a new mechanism of lipotoxicity, what we define as 'immunometabolic' lipotoxicity, and discuss the potential therapeutic implications of targeting this lipotoxicity using lipid lowering medications.